Behavior of the interaction between twin transitional round fountains in a homogeneous fluid, Part 2: Numerical study. (July 2015) - Mahmud, Hasan; Lin, Wenxian; Gao, Wenfeng; Armfield, S.W.; He, Yinghe
Abstract: This paper is the second part of our study on the behavior of the interaction between twin transitional round fountains with equal power in a homogeneous fluid. In the first part (Mahmud et al., 2015), an experimental study using PIV techniques and flow visualization was carried out over the ranges 1 ⩽ Fr ⩽ 5 and 25 ⩽ Re ⩽ 400, where Re and Fr are the Reynolds and Froude numbers, respectively. In the current paper, this work is extended to wider ranges, i.e., 1 ⩽ Fr ⩽ 10 and 25 ⩽ Re ⩽ 1000, by a series of three-dimensional direct numerical simulation (DNS). In addition, a preliminary study on the effect of the distance between the two fountain sources is also carried out for three representative cases. The DNS results are found to capture all the major features of the steady, and unsteady weakly multi-modal and strongly multi-modal interaction behavior, which is dominated by bobbing and flapping motions, as found by the experimental study (Mahmud et al., 2015), but over wider ranges of Fr and Re . Furthermore, the maximum fountain penetration height and the maximum thickness of the interaction region, obtained with the DNS, together with the experimental results of (Mahmud et al., 2015), are quantified and compared to the available scalings for single fountains in a homogeneous fluid at comparable Fr and Re values, and several scaling relations are then developed for these parameters over the ranges of Fr and Re considered in the current study.